Microanálise em trabalhos de rotina: II - Avaliação de proteínas - Brune, Walter; Braga, José Mário; Martins Batista, Cid; da Silva, Dirceu Jorge (Revista Ceres, 2025)
Three forms of the Kjeldahl process were compared with one another to determine which would be most suitable for routine work: 'Macroanalysis', in which ammonium was distilled; 'Semi- microanalysis', in which ammonium was transported by vapor; and 'Microanalysis', in which ammonium was transported by dif- fussion (Conway).